Experimental Optimization, Design Synthesis, and Up-Conversion Luminescence Properties of Y4GeO8: Er3+/Yb3+ Red Phosphors - Liu, S. Y.; Gao, D.; Wang, L.; Song, W. B.; Yin, H.; Wang, S. T,; Zhu, Y.
The Er3+/Yb3+ co-doped Y4GeO8 crystal powders were successfully synthesized us-ing a high-temperature solid-phase method. The crystal structure of the obtained phosphors was confirmed to be pure Y4GeO8 through X-ray diffraction (XRD) analysis. A regression equation correlating Er3+/Yb3+ doping concentrations with luminescent intensity was estab-lished based on the optimized theoretical model derived from experimental design. The op-timal concentrations of Er3+ and Yb3+ under 980 nm laser excitation were determined as 7.41% and 21.34%, respectively, while under 1550 nm laser excitation, the concentrations were 2.66% and 17.42%, respectively. The fluorescence emission spectra of the up-conver-sion samples were measured, revealing intense green and red emissions with peaks at 542, 546, and 654 nm under 980 nm excitation, and peaks at 546, 557, and 663 nm under 1550 nm excitation. These peaks correspond to transitions from 2H11/2 to 4I15/2, 4S3/2 to 4I15/2, and 4F9/2 to 4I15/2 energy levels. The relationship between up-conversion luminescence and laser op-erating current for the optimal samples under 980 nm and 1550 nm was investigated, uncov-ering that up-conversion luminescence occurs through both two-photon and three-photon processes. A detailed analysis and discussion of the up-conversion luminescence mecha-nisms were conducted. Furthermore, the relationship between up-conversion fluorescence and temperature for the optimal samples was studied, revealing excellent temperature-sens-ing characteristics under 980 nm and 1550 nm laser excitations. The calculated illumination region coordinates for the optimal samples under 980 nm and 1550 nm wavelength excitations were (0.5558, 0.4362) and (0.5256, 0.4687), respectively. The research highlights the potential of rare-earth ion-doped up-conversion luminescent materials for diverse anti-coun-terfeiting applications. In particular, the Y4GeO8: Yb3+/Er3+ phosphors, incorporating a dual-excitation mechanism, enhance the security of anticounterfeiting strategies in multifaceted scenarios. The study underscores the promising developments in this field.
Keywords: Physics